Prediction of time averaged wall shear stress distribution in coronary arteries’ bifurcation varying in morphological features via deep learning - Sarkhosh, Mohammad Hossein; Edrisnia, Hadis; Raveshi, Mohammad Reza; Sharbatdar, Mahkame (Frontiers in Physiology, 2025)
IntroductionUnderstanding the hemodynamics of blood circulation is crucial to reveal the processes contributing to stenosis and atherosclerosis development.MethodComputational fluid dynamics (CFD) facilitates this understanding by simulating blood flow patterns in coronary arteries. Nevertheless, applying CFD in fast-response scenarios presents challenge due to the high computational costs. To overcome this challenge, we integrate a deep learning (DL) method to improve efficiency and responsiveness. This study presents a DL approach for predicting Time-Averaged Wall Shear Stress (TAWSS) values in coronary arteries’ bifurcation.ResultsTo prepare the dataset, 1800 idealized models with varying morphological parameters are created. Afterward, we design a CNN-based U-net architecture to predict TAWSS by the point cloud of the geometries. Moreover, this architecture is implemented using TensorFlow 2.3.0. Our results indicate that the proposed algorithms can generate results in less than one second, showcasing their suitability for applications in terms of computational efficiency.DiscussionFurthermore, the DL-based predictions demonstrate strong agreement with results from CFD simulations, with a normalized mean absolute error of only 2.53% across various cases.